Приєднані гіллясті ланцюгові дроби з двома нерівнозначними змінними - Дмитришин, Р.I. (Український математичний журнал, 2014)
Построен алгоритм разложения заданного формального двойного степенного ряда в присоединенную ветвящуюся цепную дробь с двумя неравнозначными переменными и установлены условия существования такого разложения. An algorithm for the expansion of a given formal double power series in the associated branched continued fraction with two independent variables is constructed and the conditions for the existence of this expansion are established.